Factors influencing customers' willingness to participate in virtual brand community's value co-creation: The moderating effect of customer involvement. Issue 3 (22nd November 2018) - Zhao, Yang; Chen, Yawen; Zhou, Ruoxin; Ci, Yinping
Abstract : Purpose: The purpose of this paper is to explore the factors influencing customers' willingness to participate in virtual brand community's value co-creation and help companies better operating the virtual brand community. Design/methodology/approach: Based on social cognitive theory and the features of the virtual brand community, this paper constructed a model of factors influencing customers' willingness to participate in virtual brand community's value co-creation. Then this paper quantitatively analyzed the mediating effect and the moderating effect. Findings: The empirical analysis came to the following conclusions: first, in virtual brand communities, customers' willingness to participate in value co-creation would be influenced by subject factors, environment factors, brand factors and perceived value factor. Second, customer involvement is an important moderator. The more involved the customer is, the more he/she will rely on the virtual brand community. Particularly, customer involvement has a positive moderating effect on the influence of subject factors, while it has a negative moderating effect on the influence of community experience and community trust. Third, perceived value plays a significant mediating role between subject factors and customers' willingness to participate in value co-creation. Practical implications: The results of this study can help companies better understand the influence of external factors like environment and brand so that they can better operate the virtual brand community and encourage customers to contribute to the development of the community and the brand. Originality/value: Most of the existing studies focused on the formation of virtual brand communities and customers' participation behaviors, but there is limited research focusing on what contributes to customers' participation in value co-creation of virtual brand communities. This study, therefore, attempts to bridge the research gap.